Scalable Production of Recombinant Adeno-Associated Virus Vectors Expressing Soluble Viral Receptors for Broad-Spectrum Inhibition of Porcine Reproductive and Respiratory Syndrome Virus Type 2 - Xiaoming Liu; Nuo Xu; Xiaoli Song; Linlin Zhuang; Qiuping Shen; Huaichang Sun (Veterinary Sciences)
Porcine reproductive and respiratory syndrome virus (PRRSV) continues to be a major threat to the global swine industry, causing significant economic losses. To address this, we developed a scalable recombinant adeno-associated virus (rAAV)-based strategy for the delivery of soluble viral receptors (SVRs) to treat and potentially eliminate PRRSV infections. This strategy involves fusing the virus-binding domains of two key cellular receptors, sialoadhesin (Sn4D) and CD163 (SRCR5-9), with an Fc fragment. We then used an insect cell–baculovirus expression vector system to produce the rAAV-SRCR59-Fc/Sn4D-Fc vector. Through a series of optimizations, we determined the best conditions for rAAV production, including a baculovirus co-infection ratio of 0.5:1.0, an initial insect cell density of 2.0 × 106 cells/mL, a fetal bovine serum concentration of 2%, and a culture temperature of 30 °C. Under these optimized conditions, we achieved a high titer of rAAV-SRCR59-Fc/Sn4D-Fc in a 2 L bioreactor, reaching 5.4 ± 0.9 × 109 infectious viral particles (IVPs)/mL. Notably, in vitro neutralization assays using a Transwell co-culture system demonstrated a 4.3 log reduction in viral titers across genetically diverse PRRSV-2 strains, including VR2332, JXA1, JS07, and SH1705. Collectively, this study provides a robust platform for large-scale rAAV production and highlights the potential of SVR-based gene therapy to address the antigenic diversity of PRRSV-2.